Predictors of recidivism among a sample of federally sentenced sexual offenders. - Randall, Sarina A. (University of Ottawa (Canada), 1992)
The purpose of this research is to determine the factors predicting recidivism among a sample of 222 federally sentenced sex offenders. Based on social and criminal data, a number of predictor variables were significantly correlated with recidivism. These variables were regressed into models of recidivism which resulted in low levels of predictability. There were, however, three prominent factors found in each model for non-sexual offence recidivism, including age, extent of criminal history and number of geographical locations where previously convicted. The results also indicated a number of trends based on correlational data. In particular, a distinction was found between sexual and non-sexual offence recidivism. General non-sexual offence recidivism was found to be associated with extent of prior criminal history and age, while sexual offence recidivism was found to be associated with extent of sexual offence history and not influenced by age.
Keywords: Sociology, Criminology and Penology.